2020
DOI: 10.3390/proteomes8030025
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glycoproteomic Alterations in Patients with Diabetic Retinopathy

Abstract: The precise molecular mechanisms of diabetic retinopathy (DR) pathogenesis are unclear, and treatment options are limited. There is an urgent need to discover and develop novel therapeutic targets for the treatment of this disease. Glycosylation is a post-translational modification that plays a critical role in determining protein structure, function, and stability. Recent studies have found that serum glycoproteomic changes are associated with the presence or progression of several inflammatory diseases. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We also determined the abnormal glycoproteomic of FN1, AHSG, SERPINC1, C4B, HPX and ITIH1 in DR vitreous samples. Our present and Ashok et al previous works have found that the biological functions enriched in the vitreous and serum glycoproteome included positive activation cascade, regulation of protein maturation, and blood coagulation in DR; the cellular components enriched in the blood microparticle, extracellular vesicle and cytoplasmic vesicle; the molecular functions enriched in the glycosaminoglycan binding, serine-type peptidase activity and sulfur compound binding [ 22 ]. KEGG signal pathway enrichment analysis results show that the VEGF signaling pathway is the main enrichment pathway, among these N-glycosylation modified differential proteins enriched in VEGF signal pathway, we defined an N-glycosylation of TIMP-1 that plays a critical role in DR progress.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We also determined the abnormal glycoproteomic of FN1, AHSG, SERPINC1, C4B, HPX and ITIH1 in DR vitreous samples. Our present and Ashok et al previous works have found that the biological functions enriched in the vitreous and serum glycoproteome included positive activation cascade, regulation of protein maturation, and blood coagulation in DR; the cellular components enriched in the blood microparticle, extracellular vesicle and cytoplasmic vesicle; the molecular functions enriched in the glycosaminoglycan binding, serine-type peptidase activity and sulfur compound binding [ 22 ]. KEGG signal pathway enrichment analysis results show that the VEGF signaling pathway is the main enrichment pathway, among these N-glycosylation modified differential proteins enriched in VEGF signal pathway, we defined an N-glycosylation of TIMP-1 that plays a critical role in DR progress.…”
Section: Discussionmentioning
confidence: 80%
“…Accumulating evidence shows that the occurrence and development of DR is related to the abnormal modification of glycosylation. The study found that 15 glycopeptides from 11 glycoproteins were significantly changed in the serum glycoprotein group of DR patients, including fibronectin (FN1), alpha-2-HS-glycoprotein (AHSG), antithrombin-III (SERPINC1), complement C4-B (C4B), hemopexin (HPX) and inter-alpha-trypsin inhibitor heavy chain H1 (ITIH1), which these glycoproteins are associated with diabetic vascular complications [ 22 ]. In this study, we identified 107 N-glycoproteins with 156 N-glycosylation sites (6 up-regulated and 132 down-regulated) abnormal modified proteins in the DR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy is the primary cause of blindness today. Two studies analyzed diabetic retinopathy using serum and cells from the eyes (Sharma et al, 2020;Ramos-Martínez et al, 2021). Human serum was analyzed from diabetic patients with and without retinopathy.…”
Section: Diabetes-related Complicationsmentioning
confidence: 99%
“…IGPs were enriched prior to MS analysis, which identified 15 IGPs from 11 glycoproteins that were significantly altered in retinopathy. The implicated proteins included fibronectin, hemopexin, and vitronectin, which are glycoproteins involved in peptidolytic processes and in chronic low-grade inflammation (Sharma et al, 2020). Epithelial cells from the lenses of T2D patients were analyzed in the context of cataract development.…”
Section: Diabetes-related Complicationsmentioning
confidence: 99%
“…For example, we recently revealed that the alterations of N-glycopeptides were significantly associated with tumor progression in prostate and papillary thyroid carcinoma (Zhang et al, 2019). But until now, only a limited number of high-throughput glycoproteomic analyses have been carried out specifically for T2D (Miura and Endo, 2016;Sharma et al, 2020). Here, we propose that integrated proteomic and glycoproteomic analyses of human plasma will identify novel biomarkers that could provide additional insight into the pathogenesis of T2D and the assessments of which could be more accurate and sensitive for disease diagnosis than currently available test methods.…”
Section: Introductionmentioning
confidence: 99%